A review of the practice and legacy of Australian planning pioneer Margaret Feilman. Issue 1 (2nd January 2017) - Davies, Amanda; Brunner, Julie
ABSTRACT: Dr Margaret Anne Feilman (OBE) (1921–2013) was one of Western Australia's most notable and influential planners. With qualifications in architecture and planning, she pioneered an approach to town design that integrated the built form with the natural environment. Her work resulted in, inter alia, the establishment of innovative residential neighbourhoods across Western Australia. Over her 34 year professional career she subscribed to many of the philosophies of the New Town Movement, but also recognised the need to adapt British planning solutions to the Australian social, economic and environmental context. She was an advocate of individualised and situational planning and of incorporating community values and concerns. She also fiercely argued that planning schemes needed to be realistic in their scope and take account of the resources and needs of communities.